THE NORMATIVE FRAMEWORKS, PRACTICE AND CHALLENGES OF THE UNITED NATIONS/AFRICAN UNION PARTNERSHIP IN PEACEKEEPING OPERATIONS (2015)
The peacekeeping partnership between the United Nations (UN) and the African Union (AU), which started in 2002, occurred at three levels: strategic, institutional and operational. The strategic partnership involves the UN Security Council (UNSC) and the AU Peace and Security Council (PSC); the institutional partnership comprises the UN Secretariat and the AU Commission, while joint peacekeeping operations have been carried out in Sudan, Somalia and Mali. Existing studies on how to improve the partnership have focused on the operational level to the detriment of the other two. This study, therefore, moved from the minimalist view to a more comprehensive approach, by focusing on the normative frameworks, practice and challenges of the partnership. The study adopted a qualitative approach and utilised a combination of descriptive, explorative and case study research design. Purposive sampling technique was used to select respondents who had knowledge of the partnership. The respondents included officials of the UN, AU, and sub-regional organisations; military, police and civilian personnel; and academics. A total of 39 in-depth interviews were conducted in Ethiopia (12), Mali (13), Sudan (seven) and Ghana (seven). Four focus group discussions were held with police personnel of varied nationalities and peacekeeping backgrounds. Secondary data were sourced from UN and AU official documents especially the provisions of the Chapter VIII of the UN Charter, the AU Constitutive Act and the AU PSC Protocol. Others consisted of books, journal articles and conference reports. Data were subjected to descriptive content analyses. The frameworks forming the basis of the partnership embody the general principles, values, expectations and prescriptive guidelines of responsibilities of both organisations. However, both institutions lack a shared understanding of the interpretation and application of these frameworks, partly due to the unclear nature of roles. The partnership has, in practice, remained asymmetrical with the UN always taking the decisions and responsibilities. Apart from Somalia, all the joint operations are controlled by the UN, with the AU playing minimal roles. While the partnership has resulted in pragmatic and flexible responses to conflicts in Sudan and Mali, and provided a way of sharing resources, it suffers from a variety of challenges. Between the UNSC and PSC and their respective secretariat, power differential has generated mutual suspicion, disagreement, competition, coordination and bureaucratic problems. These have undermined consensus and cohesion during joint operations. In Mali and Sudan, the two organisations competed over the mission’s chain of command, disagreed on the appointment of senior officials, and took decisions without consulting each other. Although the situation was different in Somalia, both organisations continue to have contradictory approaches regarding the resolution of the conflict. A comprehensive approach to understanding the nature of the United Nations/African Union peacekeeping partnership revealed some fundamental challenges. Future partnerships should be based on mutual trust, comparative strengths, and a shared interpretation of the normative frameworks especially the Chapter VIII of the UN Charter.